Transformatif Paradigma Masyarakat Adat Semende Kota Bandar Lampung Dalam Pembagian Harta Waris Tunggu Tubang Hijrah - Muslim; Kurniati, Herlina (Jurnal Al-Qadau: Peradilan dan Hukum Keluarga Islam, 2024)
Inheritance system The Semende traditional community generally applies a female majorat kinship system, namely the eldest daughter (wait tubang) who becomes the heir. However, along with the times, there has been a paradigm shift that has occurred in a small portion of the Semende contract community, especially those in overseas lands, who no longer apply the traditional Twai Tubang inheritance system as is the case in the city of Bandar Lampung. This research aims to examine the meaning of the shift and the factors that caused the shift in the paradigm of the Semende indigenous community towards the matrilineal inheritance system. This type of research is carried out using sociological law or empirical juridical research, which is descriptive analytical in nature which describes and explains the kinship structure of the Semende indigenous community in the city of Bandar Lampung which is taken from primary data by conducting interviews and secondary data by processing data from primary legal materials and even secondary law. and tertiary legal materials. From the results of the research, it can be understood that the transformative meaning/paradigm shift of the Semende indigenous community towards the matrilineal inheritance system means that inheritance rights were previously controlled by the eldest daughter but have now undergone changes, especially assets obtained from marriage, or assets obtained from overseas land. which is known as waiting for tubang hijrah, while inheritance assets in the form of agricultural land, high inheritance land, inherited rice fields, gadang houses, will be owned and controlled by Mamak, the head of the heir. One of the reasons for the shift in the paradigm of the Semende Indigenous Community is that the Semende Indigenous Community is a dynamic society, and has a life principle of behaving with high morals, self-knowledge and a big heart. Apart from that, the shift in understanding of the Tubang inheritance system is caused by several factors, such as residential environmental factors, religious/religious factors, educational environmental factors, economic factors, mixed marriage factors, educational level factors and parental love factors for children who do not differentiate between men and women.Keywords: Semende Indigenous People; matrilineal; transformative/shifting; wait for the tube